2020
DOI: 10.1039/c9pp00420c
|View full text |Cite
|
Sign up to set email alerts
|

Amplified luminescence quenching effect upon binding of nitrogen doped carbon nanodots to transition metal ions

Abstract: The ‘J- or H-emissive aggregate model’ proposed for carbon nanodots is validated by monitoring their fluorescence quenching in different solutions with varying hydrogen bonding strengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…Most importantly, a breakthrough in the emissive aggregate model for CDs occurred when Kumbhakar's group reported experimental findings demonstrating the self‐assembly nature of certain CDs in polar solvents into typical H‐aggregates . Our research group gets motivated by these results and we validated this ‘H‐aggregate model’ by observing solvent effects on optical properties and transition metal ion‐induced amplified luminescence quenching of typical CDs . Our results recognised J‐, H‐ and JH‐ aggregate like behaviour of CDs in polar solvents.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…Most importantly, a breakthrough in the emissive aggregate model for CDs occurred when Kumbhakar's group reported experimental findings demonstrating the self‐assembly nature of certain CDs in polar solvents into typical H‐aggregates . Our research group gets motivated by these results and we validated this ‘H‐aggregate model’ by observing solvent effects on optical properties and transition metal ion‐induced amplified luminescence quenching of typical CDs . Our results recognised J‐, H‐ and JH‐ aggregate like behaviour of CDs in polar solvents.…”
Section: Introductionsupporting
confidence: 66%
“…[14,24] Our research group gets motivated by these results and we validated this 'H-aggregate model' by observing solvent effects on optical properties and transition metal ioninduced amplified luminescence quenching of typical CDs. [25,26] Our results recognised J-, H-and JH-aggregate like behaviour of CDs in polar solvents. In continuation of such previous results, it is visualised that interaction of hydrophilic CD with cationic organic drugs and proteins can be used to interrogate the aggregate structure of CDs.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Another ion that can quench the PL of CNDs is Fe 3+ [42,[114][115][116][117][118][119][120], but this is highly susceptible to interference by other metal ions. To improve the efficiency of Fe 3+ biosensors, Qian et al found that L-lysine recovers the PL quenched by Fe 3+ .…”
Section: Detection Of Fe (Iii) and The Underlying Mechanismsmentioning
confidence: 99%